Sistem Informasi Layanan Jasa Photo Studio Raja Berbasis Web - Dwiki Ilham; Muhammad Ihsan; Karnadi Karnadi (Modem : Jurnal Informatika dan Sains Teknologi., 2024)
Raja Photo Studio is a place that provides services in the field of photography, with the aim of maximizing and empowering all the potential and abilities of its founder, who was born from a background in the world of photography. The photo services in question are for people who need photos for their own purposes. such as graduation photos, pre-wedding photos, family photos and so on. Customers can book coverage for weddings and aqikah events and so on. The information available at Raja Photo Studio includes product information in the form of prices and photo sizes, sales information. Based on research regarding the Web-Based Service Information System at Studio Raja Using the Waterfall Method